Behavior and Splice Length of Deformed Bars Lapping in Spirally Confined Grout-Filled Corrugated Duct - Yongfeng Zheng; Zhangfeng Zhu; Zhengxing Guo; Peng Liu (Advances in Materials Science and Engineering)
This paper discusses the behavior of grouted noncontact lap splices under monotonic tension load. Deformed bars lapped through a grout-filled corrugated duct, and a spiral reinforcement was preembedded in the connection to improve tensile strength of the splice. The experimental results show that bond failure splices are always failed by the pullout of the preembedded bar other than the grouted bar. As the spiral pitch distance is not greater than 75 mm, the tensile strength generally improves with the increment of volumetric spiral reinforcement ratio due to the higher confinement provided by the spiral bar. Compared with the spiral bar diameter, the spiral pitch distance provides more dominant effect on the tensile strength of the connection. Based on the experimental results and the development length specified in ACI 318-14, a revised equation with a reduction factor of 0.76 was proposed to predict the required minimum lap length of spirally confined lap splice.